2020
DOI: 10.1021/acs.orglett.9b04343
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Free sp3 C-SCF3 Coupling Reactions between Cycloketone Oxime Esters and S-trifluoromethyl 4-Methylbenzenesulfonothioate

Abstract: A novel sp3 C-SCF3 coupling reaction between cycloketone oxime esters and S-trifluoromethyl 4-methylbenzenesulfonothioate was achieved. Ethanol was found to facilitate this transformation by trapping the sulfonyl cation. The metal-free and photocatalyst-free reaction conditions, as well as the broad substrate scope, make this a green protocol for the synthesis of SCF3-substituted nitriles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 48 publications
0
31
0
Order By: Relevance
“…When the 1-(2-(4-methoxyphenyl)ethyl)cyclobutanol (42c) was used as a substrate, the fluorinated product (43c) was obtained in a 40% yield. The reaction was also tolerant to the benzocyclobutenol (44) and the fluorinated ketone (45) was selectively obtained in an efficient manner (85% yield). The authors suggested a radical-type mechanism for the synthesis of 43.…”
Section: Fluorination Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the 1-(2-(4-methoxyphenyl)ethyl)cyclobutanol (42c) was used as a substrate, the fluorinated product (43c) was obtained in a 40% yield. The reaction was also tolerant to the benzocyclobutenol (44) and the fluorinated ketone (45) was selectively obtained in an efficient manner (85% yield). The authors suggested a radical-type mechanism for the synthesis of 43.…”
Section: Fluorination Reactionsmentioning
confidence: 99%
“…In 2020, Zhao and co-workers reported the synthesis of trifluoromethylthiolated nitriles at the -and -positions. [45] Taking benefit from -fragmentation reactivity of constrained cyclic compounds, a metal-free process based on the trifluoromethylthiolation of cycloalkanone oxime esters was developed. Similarly to the work of Hu and Shen, the S-(trifluoromethyl)-4-methylbenzenesulfonothioate (TolSO2SCF3) was used as the SCF3 source.…”
Section: Trifluoromethylthiolation Reactionsmentioning
confidence: 99%
“…In 2020, Zhao and co‐workers reported the synthesis of trifluoromethylthiolated nitriles at the γ‐ and δ‐positions [45] . Taking advantage of the β‐fragmentation reactivity of constrained cyclic compounds, a metal‐free process based on the trifluoromethylthiolation of cycloalkanone oxime esters was developed.…”
Section: Remote Functionalization Via β‐Fragmentationmentioning
confidence: 99%
“…Recently, Lu and co‐workers demonstrated a metal‐free coupling of cycloketone oxime esters 115 with S ‐trifluoromethyl 4‐methylbenzenesulfonothioate 116 in DMAc at 100 °C, providing a versatile route to SCF 3 ‐substituted nitriles 117 (Scheme 41). [53] Mechanistically, DMAc was regarded as the reductant to initiate the iminyl radical formation. Moreover, EtOH played a vital role in the transformation by trapping the sulfonyl cation.…”
Section: Dmac/b2(oh)4 or Dmac‐promoted Cross‐coupling Reactionsmentioning
confidence: 99%